Q-Bessel polynomials for linear phase matched filter - Singthongchai, R.; Sangaroon, O.; Janchitrapongvej, K. (My University, 2015)
In this paper, q-Bessel polynomials for linear phase matched filter is presented. In order to approximate a receiver filter with optimum performance, a raised-cosine test pulse is utilized. A transfer function of the proposed matched filter at receiver consists of transmission zero pairs and q-Bessel polynomials used as a linear phase denominator. Simulation results show that the performance of the matched filter is better than the one obtained from conventional Bessel polynomials.
Keywords: linear phase; matched filters; q-Bessel polynomials